Five new Lathys species (Araneae: Dictynidae) from South China and the first description of the male of Lathys spiralis Zhang, Hu & Zhang, 2012 - Liu, Keke; Meng, Zeyuan; Xiao, Yonghong; Xu, Xiang (Zootaxa, 2018)
Dictynidae spiders were collected from Jinggang Mountain National Nature Reserve, Jiangxi Province, China in the past four years. Five new species are described and illustrated with photographs, SEMs and line drawings: Lathys adunca Liu spec. nov. (male), L. deltoidea Liu spec. nov. (female), L. fibulata Liu spec. nov. (female), L. huangyangjieensis Liu spec. nov. (male, female) and L. zhanfengi Liu spec. nov. (female). Both sexes of the species L. spiralis Zhang, Hu & Zhang, 2012 were collected from leaf litter in Jinggangshan University and the male is described for the first time. All specimens are deposited in the Animal Specimen Museum, Life Science College, at the Jinggangshan University (ASM-JGSU).